Health Iniquity, Unhealthy Behavior, and Coverage of Mammography in Brazil - Sabrina Daros Tiensoli; Mariana Santos Felisbino-Mendes; Gustavo Velasquez-Melendez (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To investigate the prevalence of mammography screening and the association among socio-demographic, behavior factors and non-adherence to mammography screening among women between 50 and 69 years old, using data from Vigitel 2016. Method: Cross-sectional, population-based study with data from Vigitel including 12,740 women in the 50-69 age group. The variables were analyzed using logistic regression. Results: Among the women studied, 21.8% had not had a mammography in the past 2 years. The characteristics associated with non-adherence to the test were having less than 12 years of education (p<0.001), having no partner (p=0.001), being underweight (p=0.002), having a negative self-perceived health status (p<0.001) and having at least one negative health behavior (p<0.001). Conclusion: There is a subgroup of women with markers of social vulnerability, which reflect the inequality in mammography screening.